PENGARUH KOMPENSASI, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PUSKESMAS ARJASA - Amin, Bahrul; Anwar, Syaiful (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
The aim of this research is to determine partially or jointly the influence of remuneration variables, work discipline and work motivation on the performance of Aljasa Community Health Center employees. Data collection was carried out through distributing questionnaires and research was conducted on 80 respondents from the civil service department (a sample of 67 civil servant workers from the Community Health Center Arjasa). Respondent responses were processed using multiple regression analysis, t-test, f-test, and r-test using a Likert scale. The results of this research reveal a partial (significant) influence between reward variables, work discipline, and work motivation on the dependent variable performance employees, while the research variables reward, job reveal the influence of work discipline variables on discipline. Work motivation for employee performance. The results of this research show that the leadership of the Arjasa Health Center can pay attention to compensation and work discipline, motivate employees and monitor employee activities to improve the performance of Puskesmas employees.